Anti-inflammatory activity study and vitamin C analysis of fruit wine from "BIKA" vitis quadrangularis wall (Vitaceae). - Camillon, Imee Ruth Brasileno
Bika Vitis quadrangularis Wall fruits are non-toxic raw material for wine making. Cytotoxicity test using the Brine Shrimp Assay showed that the crude ethanolic extract has an LC50 higher than 1000 ug/mL., Using the Standard Iodine Method, "bika" fruit was found to contain 789 ppm vitamin C however, analysis of the "bika" wine showed a lower amount (10.8-29.1 ppm vitamin C). Using the Carrageenan-Induced Edema Assay, "bika" fruit was observed to have a notable anti-inflammatory activity. The crude ethanolic extract and the positive control showed a 75.0% and 38.5% inhibitions respectively, with the latter at a lower concentration than the extract. "Bika" wine's anti-inflammatory activity was slightly lower than the fruit. The wine showed a percentage inhibition of 30.2-56.6%. The first five days of the fermentation was the peak of the yeast activity as indicated by a significant change in the specific gravity, pH and total acidity of the must.